193k views
3 votes
Express your answer as a polynomial in standard form.f (x) = 3x2 + x - 1g(x) = -3x + 5Find: g(f (2)το τες

Express your answer as a polynomial in standard form.f (x) = 3x2 + x - 1g(x) = -3x-example-1

1 Answer

5 votes

Given the two polynomials, we are looking for the composite function g(f(x)). We will insert the value of f(x) to the function g(x). We have


g(f(x))=-3(3x^2+x-1)+5

Simplifying the obtained algebraic expression above


\begin{gathered} g(f(x))=-9x^2-3x+3+5 \\ g(f(x))=-9x^2-3x+8 \end{gathered}

Hence, the answer to this problem is


g(f(x))=-9x^2-3x+8

User Illya Krit
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.